1993
DOI: 10.1038/362040a0
|View full text |Cite|
|
Sign up to set email alerts
|

Microsecond-resolved XAFS of the triplet excited state of Pt2(P2O5H2)4–4

Abstract: Little is known about the excited-state structures of most inorganic compounds. Time-resolved resonance Raman and time-resolved infrared spectroscopies can provide only indirect structural information for short-lived excited species in solution at room temperature. Time-resolved X-ray diffraction has the potential to give more direct information, but no excited-state structures have yet been reported; picosecond gas-phase electron diffraction has been proposed recently, but not yet demonstrated. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 17 publications
7
61
0
1
Order By: Relevance
“…30,31 In 1993, Thiel et al reported 0.52 « 0.13 ¡ contraction in the PtPt distance in a liquid phase by EXAFS. 32 Other diffraction studies reached basically similar results indicating the contraction of PtPt distance in the excited state. In 1980, X-ray diffraction studies of a ground state K 4 [Pt 2 (pop) 4 ] crystal were first carried out by Sadler et al, who found the PtPt distance to be 2.925 ¡.…”
Section: Step I: Crystal Packing Approachsupporting
confidence: 69%
“…30,31 In 1993, Thiel et al reported 0.52 « 0.13 ¡ contraction in the PtPt distance in a liquid phase by EXAFS. 32 Other diffraction studies reached basically similar results indicating the contraction of PtPt distance in the excited state. In 1980, X-ray diffraction studies of a ground state K 4 [Pt 2 (pop) 4 ] crystal were first carried out by Sadler et al, who found the PtPt distance to be 2.925 ¡.…”
Section: Step I: Crystal Packing Approachsupporting
confidence: 69%
“…Initially, the time resolution of these studies was limited to the ms-ns range [139][140][141][142], except for one groundbreaking case [143].Theoretical and experimental critical issues had to be considered to extend the feasibility of time-resolved XAS characterization to the sub-ns time domain.…”
Section: X-ray Transient Absorption: Theoretical Background and Expermentioning
confidence: 99%
“…A second study, based on Raman data and using the empirical Badger's rule, which relates a change in stretching frequency with a change in bond length, leads to a value of 2.81 A Ê (Stein et al, 1983). EXAFS results have been used to derive a contraction of 0.52 (13) A Ê of the P planes along the PtÐPt axis but are based on an assumed PtÐPt excited-state distance of 2.75 A Ê (Thiel et al, 1993). Theoretical DFT (density functional theory) calculations of the excited-state structure, to be published elsewhere (Novozhilova & Coppens, 2001), con®rm the shortening of the PtÐPt bond, though the theoretical value is quite dependent on the functionals used in the calculation.…”
Section: The Contraction Of the Ptðpt Bondmentioning
confidence: 99%
“…The results indicate the feasibility of the approach, and point the way for the further re®nement of the methods employed. triplet state has been previously investigated by spectroscopic techniques (Rice & Gray, 1983;Stiegman et al, 1987) and by EXAFS (Thiel et al, 1993). The excited state is split into 3 E u and 3 A 1u levels, with a spacing of only 42 cm À1 (Fig.…”
Section: Introductionmentioning
confidence: 99%